2016
DOI: 10.1002/2015jd024650
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric residence times from transpiration and evaporation to precipitation: An age‐weighted regional evaporation tagging approach

Abstract: The atmospheric water residence time is a fundamental descriptor that provides information on the timescales of evaporation and precipitation. In this study, a regional climate model-based evaporation tagging algorithm is extended with an age tracer approach to calculate moisture residence times, defined as time between the original evaporation and the returning of water masses to the land surface as precipitation. Our case study addresses how long this time is for the transpired and for the direct evaporated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 83 publications
0
28
0
Order By: Relevance
“…The atmospheric branch of the hydrological cycle simulated by a climate model can be examined with a surface evaporation tagging method, which consists in tracking the evaporated water online, that is throughout the model run, from a source region until it precipitates or is advected outside of the simulation domain (Arnault, Knoche, et al, 2016;Dominguez et al, 2016;Insua-Costa & Miguez-Macho, 2018;Knoche & Kunstmann, 2013;Sodemann et al, 2009;Wei et al, 2015Wei et al, , 2016. It is noted that Arnault, Knoche, et al (2016) and Dominguez et al (2016) and Insua-Costa and Miguez-Macho's (2018) tagging methods were independently developed in the WRF model.…”
Section: Introductionmentioning
confidence: 99%
“…The atmospheric branch of the hydrological cycle simulated by a climate model can be examined with a surface evaporation tagging method, which consists in tracking the evaporated water online, that is throughout the model run, from a source region until it precipitates or is advected outside of the simulation domain (Arnault, Knoche, et al, 2016;Dominguez et al, 2016;Insua-Costa & Miguez-Macho, 2018;Knoche & Kunstmann, 2013;Sodemann et al, 2009;Wei et al, 2015Wei et al, , 2016. It is noted that Arnault, Knoche, et al (2016) and Dominguez et al (2016) and Insua-Costa and Miguez-Macho's (2018) tagging methods were independently developed in the WRF model.…”
Section: Introductionmentioning
confidence: 99%
“…The global average time a water molecule spends in the atmosphere is 8-10 days (e.g., Bodnar et al, 2013;Bosilovich & Schubert, 2002;Chow et al, 1988;Jones, 1997;Trenberth, 1998;Van der Ent & Tuinenburg, 2017;Ward & Robinson, 2000;Yoshimura et al, 2004). Only recently, the regional differences in atmospheric residence times have been reported (Läderach & Sodemann, 2016;Van der Ent et al, 2014;Van der Ent & Tuinenburg, 2017;Wei et al, 2016). Van der Ent and Tuinenburg (2017) defined evaporation residence times at location x as the time a water particle at location x will spend in the atmosphere from the moment it evaporates until it returns to the Earth surface as precipitation at any location.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have estimated PE as the precipitation amount divided by the mass of associated moisture sources, but the definition may vary with the specific context of water budget estimation. For example, PE can be defined as the ratio of precipitation rate to the sum of the surface evaporation and water vapor convergence from the perspective of large-scale water vapor budgets [28][29][30]. It can also be defined as the ratio of precipitation rate to the vertical integral of condensation and deposition rates derived from the cloud microphysical budget [9,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…As PE is the reciprocal of atmospheric water residence time, its variability is closely associated with the activity of the East Asia summer monsoon (EASM) [19,21]. Wei et al [29] suggested that different age patterns of tagged precipitation in Southeast China reflect the varying impact of the EASM through prevailing wind directions and wind speeds.…”
Section: Introductionmentioning
confidence: 99%